Clinical and functional outcomes in patients submitted to early versus late surgery for lumbar disc herniation: A systematic review - Alana Thuane Rutzen, MD; Rafael D'agostini Annes, MD; Shana Ginar da Silva, PhD (Interdisciplinary Neurosurgery, 2022)
To verify clinical and functional outcomes in patients submitted to early versus late surgery for lumbar disc herniation. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for systematic reviews and Meta-analysis, a systematic review was conducted in MEDLINE/PubMed, Web of Science, and Scopus from September to November 2019. From the 31,901 titles identified, after rigorously following the proposed methodology, the review resulted in n = 10 studies that met the eligibility criteria and were included in the review. Among these, two were considered from the early surgery group, four from the late surgery group, and in four studies it was not possible to identify the time of the surgical procedure. The included studies presented marked heterogeneity in relation to the evaluation instruments used to measure pain and to evaluate the functional capacity of the patients, as well as the different moments adopted to perform the postoperative and follow-up evaluations. Based on the available evidence, we conclude that the available literature in the area is not sufficient to state whether there is a benefit of early surgery for herniated lumbar disc in favor of late surgery in the clinical and functional outcomes assessed.